2020
DOI: 10.1021/acschemneuro.0c00343
|View full text |Cite
|
Sign up to set email alerts
|

Classics in Neuroimaging: Development of Positron Emission Tomography Tracers for Imaging the GABAergic Pathway

Abstract: Advances in drug discovery and diverse radiochemical methodologies have led to the discovery of novel positron emission tomography (PET) radiotracers used to image the GABAergic system, shaping our fundamental understanding of a variety of brain health illnesses, including epilepsy, stroke, cerebral palsy, schizophrenia, autism, Alzheimer’s disease, and addictions. In this Viewpoint, we review the state-of-the art of PET imaging with radiotracers that target the GABAA–benzodiazepine receptor complex, challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…To accurately measure GABA release, PET tracers with enhanced sensitivity to GABA are necessary, which could be widely used to evaluate GABA transmission in vivo across various disorders and enable assessment of region-specific changes . This capability to separately image each GABA A subtype, GABA B , and other components (such as GABA transporters and glutamate decarboxylases) in vivo would significantly advance our understanding of the neurobiology of GABA in both healthy and diseased states …”
Section: Pet Tracers For Anesthesia-related Receptorsmentioning
confidence: 99%
“…To accurately measure GABA release, PET tracers with enhanced sensitivity to GABA are necessary, which could be widely used to evaluate GABA transmission in vivo across various disorders and enable assessment of region-specific changes . This capability to separately image each GABA A subtype, GABA B , and other components (such as GABA transporters and glutamate decarboxylases) in vivo would significantly advance our understanding of the neurobiology of GABA in both healthy and diseased states …”
Section: Pet Tracers For Anesthesia-related Receptorsmentioning
confidence: 99%
“…Hence, disruptions in the GABAergic system could lead to an imbalance between the two neurotransmission systems and are associated with the pathogenesis of various CNS diseases, such as epilepsy, schizophrenia, Parkinson’s disease, and Alzheimer’s disease [ 4 ]. The GABAergic system is therefore a prime target of several CNS-targeted drugs [ 5 ], even though the exact role of GABA in these disorders is not fully understood. Non-invasive imaging of the GABAergic system could aid to understand this role.…”
Section: Introductionmentioning
confidence: 99%
“…Several imaging methods have been developed for GABA receptors, with the benzodiazepine derivatives [ 11 C]flumazenil ( [ 11 C]2 ), [ 18 F]flumazenil ( [ 18 F]2 ), and [ 11 C]Ro15-4513 ( [ 11 C]3 ) frequently being used as positron emission tomography (PET) tracers for the GABA A receptor (Fig. 2 ) [ 5 , 6 ]. For example, clinical studies using these radioligands include applications in schizophrenia, major depressive disorder, Alzheimer’s disease, and autism spectrum disorder [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we sought to address this issue by using state-of-the-art imaging transcriptomics to (1) uncover patterns of co-expression between genes encoding GABA A R subunits and inhibitory interneuron markers in the human brain, and to (2) decode their links to the binding distribution patterns of two gold-standard GABA PET radiotracers, [ 11 C]Ro15-4513 and [ 11 C]flumazenil 28 . We found that distinct GABAergic inhibitory interneuron marker genes co-expressed with specific GABA A R subunit-encoding genes.…”
Section: Introductionmentioning
confidence: 99%